Pulmonary Hemodynamic Changes with Nitric Oxide or Oxygen in a Patient with Asplenia, Single Right Ventricle, and Total Anomalous Pulmonary Venous Connection after Fontan Procedure - Hideharu Oka; Kouichi Nakau; Aya Kajihama; Masaya Sugimoto; Hiroshi Azuma (Case Reports in Cardiology)
Asplenia syndrome is frequently complicated by a total anomalous pulmonary venous connection. Pulmonary venous obstruction, following total anomalous pulmonary venous connection surgery, is one of the risk factors for morbidity and mortality. In some patients, the pulmonary vasculature is abnormal even in the absence of clinical evidence of pulmonary venous obstruction. We hypothesized that a change in the pulmonary hemodynamics could indicate the abnormality of pulmonary vein in a patient with asplenia, single right ventricle, and total anomalous pulmonary venous connection, following Fontan procedure. Here, we present a case of asplenia, single right ventricle, total anomalous pulmonary venous connection, and right pulmonary venous obstruction in which evidence of a potential left pulmonary venous obstruction was obtained following the administration of inhaled nitric oxide and oxygen.